Cannabinoid Receptor Signaling in Central Regulation of Feeding Behavior: A Mini-Review - Koch, Marco (Frontiers in Neuroscience, 2017)
Cannabinoids are lipid messengers that modulate a variety of physiological processes and modify the generation of specific behaviors. In this regard, the cannabinoid receptor type 1 (CB1) represents the most relevant target molecule of cannabinoids so far. One main function of central CB1 signaling is to maintain whole body energy homeostasis. Thus, cannabinoids functionally interact with classical neurotransmitters in neural networks that control energy metabolism and feeding behavior. The promotion of CB1 signaling can increase appetite and stimulate feeding, while blockade of CB1 suppresses hunger and induces hypophagia. However, in order to treat overeating, pharmacological blockade of CB1 by the inverse agonist rimonabant not only suppressed feeding but also resulted in psychiatric side effects. Therefore, research within the last decade focused on deciphering the underlying cellular and molecular mechanisms of central cannabinoid signaling that control feeding and other behaviors, with the overall aim still being the identification of specific targets to develop safe pharmacological interventions for the treatment of obesity. Today, many studies unraveled the subcellular localization of CB1 and the function of cannabinoids in neurons and glial cells within circumscribed brain regions that represent integral parts of neural circuitries controlling feeding behavior. Here, these novel experimental findings will be summarized and recent advances in understanding the mechanisms of CB1-dependent cannabinoid signaling being relevant for central regulation of feeding behavior will be highlighted. Finally, presumed alternative pathways of cannabinoids that are not driven by CB1 activation but also contributing to control of feeding behavior will be introduced.